Can you learn not to respond to irrelevant motion while making fast arm movements? - Eli Brenner; Lara M. de Jonge; Niels J. J. Tiems; Glenn Rosenquist; Thijs Wiggers; Jeroen B. J. Smeets; Emily M. Crowe (PLoS ONE, 2025)
If the target of a goal-directed arm movement is suddenly displaced, the movement is quickly adjusted in accordance with the target’s new position. Such quick adjustments are even observed if the target is moving, so the arm is moving towards a future target position. If irrelevant items near that future position suddenly start moving, the arm produces a futile response in the direction of the irrelevant items’ motion. We wondered whether people could learn not to respond to such irrelevant motion. To find out, we had participants intercept targets that moved across a background consisting of hundreds of small dots (irrelevant items). At a fixed time before the target reached an interception zone, the background dots started moving. The response to this irrelevant motion declined across the first few hundred trials, but it never fully disappeared. Including trials in which the target jumped established that participants learnt to reduce their response to the irrelevant motion, rather than to reduce their response to any new information. We conclude that participants can reduce the extent to which they respond to irrelevant motion, but that they cannot suppress such responses altogether.